2007
DOI: 10.1149/1.2737541
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Capacitor of MnFe[sub 2]O[sub 4] with Organic Li-Ion Electrolyte

Abstract: MnFe 2 O 4 nanocrystallites have been found to exhibit capacitive characteristics in organic electrolyte containing 1 M LiPF 6 in a mixture of ethyl carbonate + ethylene methyl carbonate up to 4.5 V vs Li/Li +. The ferrite exhibits a capacitance of 126 F/g-MnFe 2 O 4 , and the symmetric-cell demonstrated a stable working voltage window of 2.5 V. In situ synchrotron spectroscopic analysis identified valence change at Mn-ion sites and a very small ͑Ͻ1%͒ extent of lattice variation, in response to Li-ion insertio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 18 publications
0
18
0
4
Order By: Relevance
“…As shown in Figure 9 a-d, the electrospun polycrystalline ZnFe 2 O 4 NFs composed of 11 nm nanocrystal building blocks are self-assembled into intertwined porous nanowebs with a continuous framework. Furthermore, the rate capability examined by galvanostatic cycling at various current densities for 55 cycles (Figure 9 e) [21] and MnFe 2 O 4 , [115][116][117] are also investigated as pseudocapacitive materials for high-performance ECs. Furthermore, the rate capability examined by galvanostatic cycling at various current densities for 55 cycles (Figure 9 e) [21] and MnFe 2 O 4 , [115][116][117] are also investigated as pseudocapacitive materials for high-performance ECs.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 9 a-d, the electrospun polycrystalline ZnFe 2 O 4 NFs composed of 11 nm nanocrystal building blocks are self-assembled into intertwined porous nanowebs with a continuous framework. Furthermore, the rate capability examined by galvanostatic cycling at various current densities for 55 cycles (Figure 9 e) [21] and MnFe 2 O 4 , [115][116][117] are also investigated as pseudocapacitive materials for high-performance ECs. Furthermore, the rate capability examined by galvanostatic cycling at various current densities for 55 cycles (Figure 9 e) [21] and MnFe 2 O 4 , [115][116][117] are also investigated as pseudocapacitive materials for high-performance ECs.…”
Section: Methodsmentioning
confidence: 99%
“…[101] Daher ist eine verbesserte Ausgangsspannung der vollständigen Zelle zu erwarten, wenn diese mit einem herkçmmlichen Kathodenmaterial wie LiCoO 2 verbunden wird. Die verbesserte elektrochemische Leistung von ZnFe 2 O 4 -NFs kann dem kontinuierlichen Gerüst aus Nano- [21] und MnFe 2 O 4 , [115][116][117] werden auch als pseudokapazitive Materialien für Hochleistungs-EKs untersucht. [12] Seit dem ersten Bericht über eine Verwendung von nanokristallinem ZnFe 2 O 4 und Ag-dotierten ZnFe 2 O 4 -Dünnschichten als Anoden für LIBs [112] gab es zahlreiche Versuche, die Leistung der ZnFe 2 O 4 -Anodenmaterialien mit verschiedenen Strukturen und Morphologien auf Grundlage verschiedener Synthesestrategien weiter zu optimieren, z.…”
Section: Ferriteunclassified
“…[12] Seit dem ersten Bericht über eine Verwendung von nanokristallinem ZnFe 2 O 4 und Ag-dotierten ZnFe 2 O 4 -Dünnschichten als Anoden für LIBs [112] gab es zahlreiche Versuche, die Leistung der ZnFe 2 O 4 -Anodenmaterialien mit verschiedenen Strukturen und Morphologien auf Grundlage verschiedener Synthesestrategien weiter zu optimieren, z. [116] Des Weiteren wurde eine asymmetrische Acetylenruß/MnFe 2 O 4 -Zellkonfiguration mit solch einem organischen Elektrolyten hergestellt. [54] Srinivasan et al [12] haben eine vergleichsweise kostengünstige und einfache Elektrospintechnik zur Synthese von Nanogeweben entwickelt, die aus verwobenen ZnFe 2 O 4 -NFs bestehen, und die erhaltenen Nanogewebe anschließend als umweltverträgliche Anode in LIBs eingesetzt.…”
Section: Ferriteunclassified
See 1 more Smart Citation
“…Therefore, great efforts have been devoted to searching for low cost alternative materials with enhanced characteristics. Mixed metal oxides and binary metal oxide/ hydroxides [14,15], possessing multiple oxidation states and structures that enable multiple redox reactions, have been reported to exhibit a higher performance than single component oxides/hydroxides, such as short ion transport pathways, superior electron collection efficiency, and fascinating synergetic properties or multifunctionalities of components [16,17]. Researchers have demonstrated that the full range of potential of the hierarchical manostructure arrays' performance could be realized [18][19][20].…”
Section: Introductionmentioning
confidence: 99%